PREFERENSI KONSUMEN GULA PASIR TERHADAP PRODUK, HARGA, PROMOSI, DAN DISTRIBUSI - Amarullah Sofa (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2019)
Introduction: Distribution system of PTPN XI depends on the tender of regulation that affects benefit for PTPN XI. Java Seven Samurai which act as bidders. This study is expected to provide important information on PTPN XI and stimulus-dependent regulation of Seven Samurai, in order to sell new sugar products directly to the consumer so that the resulting higher profits.Methods: This research is a non-experimental study that performs data collection at a certain time for the sample group (cross-sectional). The research approach used in this study is a qualitative descriptive analysis approach to processing primary data obtained from the research sample.Results: The results of this study, new favorite sugar characteristics are: 1) Product: consumers prefer brands using Indonesian sugar, sugarscrystals are white clearly color, and odorless; 2) Price: consumers like discounts and bonuses given to purchase a lot and adjust the size of the price change per pack; 3) Promotion: social media are easily found and preferred customer is Facebook; 4) Distribution: traditional marketing is a consumer preferred shop and agents while modern retail customers preferred is a minimarket.Conclusion and suggestion: Sugar is distributed directly from PTPN XI preferably at minimarket and agents. While distribution is lacking indirectly (through an agent) is a traditional store.